The nexus between organized crime and terrorism in Sahel (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The states that make up the Sahelian region were born with economic, political-administrative, and social issues, that has made them, today, fertile ground for the emergence and spread of a wide range of non-state groups. In particular, terrorism and organized crime generate unprecedented relationships within power gaps, which contribute to perpetuating spirals of violence, which further destabilize the precarious conditions of the Sahel.
Keywords: crime-terror nexus, Sahel, organized crime, jihadist terrorism, AQIM